2017
DOI: 10.1177/0892705717712634
|View full text |Cite
|
Sign up to set email alerts
|

Rotomolded antistatic and flame-retarded graphite nanocomposites

Abstract: Graphite nanoplatelets with an average particle size of 13 μm and an estimated flake thickness of about 76 nm were prepared by microwave exfoliation, followed by ultrasonication-assisted liquid phase delamination, of an expandable graphite. This nano-additive was used to fabricate linear low density polyethylene (LLDPE) and poly(ethylene-co-vinyl acetate) (EVA) based nanocomposite sheets using rotational moulding. The dry blending approach yielded surface resistivities within the static dissipation range at fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…Following this, many studies investigating the possibility of producing composites via rotational molding were conducted. Different natural fibers such as flax [10], banana and abaca [11], agave [12][13][14], coir [12,14,15], pine [12], maple [16,17], wood [18,19], buckwheat husk [20], glass fibers [21,22], carbon fibers [22], glass particles [23,24], other synthetic particles [24,25] and nanoparticles [26][27][28][29][30] as reinforcements with different grades of polyethylene [9,11,12,14,15,17,21,22,31], polyamide [26], polylactic acid [13,20], and polypropylene [18] as matrix were used in the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Following this, many studies investigating the possibility of producing composites via rotational molding were conducted. Different natural fibers such as flax [10], banana and abaca [11], agave [12][13][14], coir [12,14,15], pine [12], maple [16,17], wood [18,19], buckwheat husk [20], glass fibers [21,22], carbon fibers [22], glass particles [23,24], other synthetic particles [24,25] and nanoparticles [26][27][28][29][30] as reinforcements with different grades of polyethylene [9,11,12,14,15,17,21,22,31], polyamide [26], polylactic acid [13,20], and polypropylene [18] as matrix were used in the studies.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Inorganic contents like wollastonite, calcium carbonate, graphite, as well as silica have been studied in the rotational molding procedure. [6][7][8][9] Zepeda-Rodríguez et al utilized carbon nanofiber to prepare LMDPE/CNF nanocomposites by rotational molding and to determine the effect of CNF surface modification on the properties of rotomolded parts. Their results showed that the mechanical properties can be significantly modified with very low CNF content (1 wt% or less), especially the surface treated one.…”
Section: Introductionmentioning
confidence: 99%
“…GNPs have high aspect ratio and surface area, low mass density, and excellent thermal, electrical, and mechanical properties [2,3,5,6,[8][9][10][12][13][14]. Recent application of GNPs in different polymers demonstrates improvement in thermomechanical characteristics [7,[15][16][17][18][19][20][21][22][23], electrical behavior [15,17,20,24], and corrosion resistance [25] of nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…GNPs have been prepared previously, using different methods [5,8], but the exfoliation of intercalated graphite (GIC), followed by mechanical agitation, remains to be the most common approach [1,2,4,5,7,[9][10][11][13][14][15]17,[23][24][25][26][27][28][29][30]. In this method, GIC (natural graphite intercalated with acids or alkali metals) undergoes exfoliation by thermal treatment or microwave irradiation, to produce exfoliated graphite (EG).…”
Section: Introductionmentioning
confidence: 99%